Balun LNA Thermal Noise Analysis and Balancing With Common-Source Degeneration Resistor - Mohammad Abubaker, Qusai (2020)
The Balun low noise amplifier (LNA) is an LNA that exploits a combination of a common-source (CS) and a common-gate (CG) transistors, which cancels the noise and distortion of the CG stage. And since the CG is known to be linear, only the CS needs to be carefully designed and optimized. The Balun LNA also cancels the distortion and noise of the CG. In this paper, the CS section will be fully analyzed, and shown how the condition set in the literature review still satisfy the balancing output and cancel the CS stage thermal noise as well as the CG thermal noise. Also, forward body biasing (FBB) is used to reduce the threshold voltage and an addition of CS degeneration resistor to balance the output while still canceling the thermal noise of the transistors is tested using UMC180nm on Cadence. The LNA achieves a gain of 19-16dB, NF <; 3.6 over the bandwidth 200M-1.9GHz without a CS degeneration. A 17.8-14.8dB gain, a NF <; 3.8 over the bandwidth 200MHz-2.1GHz and power consumption of 12mW in both cases. Although outside the bandwidth, at ISM 2.4GHz a gain of 14.5dB and a NF of 3.8 is achieved, making it suitable for wireless sensor node (WSN) applications. According to the author's knowledge, this is the first time the degeneration resistor noise analysis on a Balun LNA is derived and analyzed.